Research on Rural Revitalization Strategy Driven by Digital Economy - Liu, Zhenyan; Cong, Riyu (Transactions on Economics, Business and Management Research, 2024)
This study deeply discusses the important role and role of the digital economy in the rural revitalization strategy. With its unique advantages, the digital economy provides a strong impetus for rural revitalization. The internal mechanism of the digital economy and how it integrates and promotes each other with the rural revitalization strategy are all important contents of this study.  Studying the relationship between digital economy and rural revitalization not only helps us understand the internal mechanism and development trend of digital economy, but also helps us to formulate more scientific and reasonable rural development policies.